2023
DOI: 10.1093/pubmed/fdad120
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT in the higher education environment: perspectives from the theory of high order thinking skills

Abstract: ChatGPT is a form of technological progress in the 5.0 era. The use of ChatGPT has begun to penetrate all fields of science, including the field of education. Students use ChatGPT to help them complete their assignments in the university environment. Apart from providing many benefits, ChatGPT also has many dangers threatening students. One of the dangers for students who rely too much on ChatGPT is a decrease in higher-order thinking skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, the emergence of LLMs may significantly streamline writing endeavors, raising concerns about the potential impact on the development of reasoning skills. Should students overly depend on text passages supplied by ChatGPT or analogous tools, there exists a risk of foregoing essential engagement in critical thinking and problem-solving processes vital for cognitive enhancement [36]. This escalating concern pertains to the potential erosion of peoples' capacity to generate original ideas and construct cogent arguments substantiating their perspectives [37].…”
Section: Losing Skills Via Substitutionmentioning
confidence: 99%
“…However, the emergence of LLMs may significantly streamline writing endeavors, raising concerns about the potential impact on the development of reasoning skills. Should students overly depend on text passages supplied by ChatGPT or analogous tools, there exists a risk of foregoing essential engagement in critical thinking and problem-solving processes vital for cognitive enhancement [36]. This escalating concern pertains to the potential erosion of peoples' capacity to generate original ideas and construct cogent arguments substantiating their perspectives [37].…”
Section: Losing Skills Via Substitutionmentioning
confidence: 99%
“…However, a recent study [26] found that accuracy and reliability are considered the most common obstacles faced when using ChatGPT in education. Challenges affiliated with reliability involve depending on biased information (i.e., restricted range of data used) [27,28], the lack of updated information (i.e., updated information stopped in 2021) [29] and providing inaccurate/fake data (i.e., presenting fabricated references) [30]. Moreover, the over-reliance on ChatGPT may have a negative effect on students' ability to think critically and solve problems [31,32].…”
Section: Drivers and Consequences Of Chatgpt In Higher Educationmentioning
confidence: 99%
“…Some scholars are convinced that some students depended on ChatGPT-generated solutions rather than using their cognitive skills to think critically and respond to situations. Over time, this reliance may erode students' critical thinking and problem-solving abilities [40]. Given the circumstances, this is highly likely because ChatGPT acquires knowledge from text data found on the internet, encompassing various sources.…”
Section: Table4 Tests Of Between Subjects Effectsmentioning
confidence: 99%